"Sugary drinks" and graphic warning labels: Critique of a recent U.S. study of parents' beverage choices for their children. Issue 1 (28th July 2022) - Rossiter, John R.
Abstract: A laboratory experiment by U.S. public health researchers Hall et al. claimed to demonstrate that a graphic picture‐and‐text warning label placed on so‐called sugary drinks would substantially reduce parents' purchase of them for their children. Hall et al., however, misclassified the alleged "sugary drinks, " omitting those containing natural but equally harmful sugars such as fructose in fruit juice and lactose in milk. They also implied that artificially sweetened "non‐sugary" drinks are harmless when available research indicates otherwise. The experiment was further invalidated by the fact that warning labels are illegal in the U.S., and those that Hall et al. used would not be permitted in any case because they partially obscured the manufacturer's brand label. There were many other methodological problems with Hall et al.'s experiment, among them the failure to do what any competent consumer researcher would do—namely ask the parents afterwards why they made the choices that they did.